Cerebral infarction complicating intravenous immunoglobulin therapy in a patient with Miller Fisher syndrome. Issue 6 (1st June 2000) - Turner, Benjamin; Wills, Adrian J
Abstract : Intravenous immunoglobulin (IVIg) therapy is being increasingly used in a wide range of neurological conditions. However, treatment is expensive and side effects may be severe. A patient with Miller Fisher syndrome who developed cortical blindness as a consequence of occipital infarction precipitated by IVIg is reported on.